Comparison of Microbiota in Zirconia and Titanium Implants: A Qualitative Systematic Review - Majid Bonyadi Manesh; Neda Vatankhah; Fatemeh Bonyadi Manesh (International Dental Journal)
Background: In this systematic review, we examine the variations in microbiota on zirconia versus titanium implants, providing insights into their impact on dental health and outcomes. The ongoing discussion regarding whether to use zirconia or titanium for implants underscores the significance of microbiota colonization in determining the longevity and performance of implants. Methods: Research questions were formulated following the Participants, Intervention, Comparison, and Outcomes framework, and a PROSPERO protocol was registered. A thorough systematic search was carried out in PubMed, Embase, and Web of Science. Two reviewers independently assessed the reports against the Participants, Intervention, Comparison, and Outcomes criteria, including the inclusion and exclusion criteria. Risk of bias was assessed using the Quality Assessment Tool for In Vitro Studies (QUIN Tool). Results: Of the 2063 articles identified, 19 articles fulfilled the inclusion criteria and subjected to quality assessment. All of the included studies were in vitro research with low (31.5%) or moderate (36.8%) or high (31.5%) risk of bias and reported data from 2 implant abutments. Zirconia implants displayed a higher occurrence of Gram-negative bacteria, such as Tannerella, Aggregatibacter, and Porphyromonas. In contrast, titanium implants showed a greater prevalence of Gram-positive bacteria, including Streptococcus, Lactobacillus acidophilus, and Staphylococcus species. Conclusion: According to the findings of the current study, both zirconia and titanium implants support the growth of different microorganisms. There were also differences in the quakity and the quantity of microorganisms detected on each material. These differences in microbial profiles indicate that the selection of implant material might impact the microbial ecosystem on the implant surface, potentially affecting clinical outcomes such as infection rates and the longevity of the implant.